(untitled) (Eurasian Journal of Religious Studies, 2025)
This study is devoted to the analysis of the religious situation in Kazakhstan and Central Asia during the Soviet period. In the first quarter of the 20th century, under ideological pressure and atheist policies, the features of religious life, the role of Islamic scholars, and the preservation of religious education among the population were examined. The main purpose of the study is to investigate the religious activities and scientific legacy of Duysenbek Kabylanbaiuly in order to identify the mechanisms for preserving Islamic traditions during the Soviet period, as well as religious consciousness and spiritual enlightenment. The study aims to demonstrate scientific methods for adapting Islamic norms to public life. The scientific significance of the work lies in the analysis of religious life in the Soviet period within a historical and social context, which allows revealing certain aspects of Islamic history. The practical significance is the possibility of applying the research results in the fields of religious education, spiritual upbringing, and the preservation of cultural heritage. The study employed historical-scientific methods, comparative analysis, examination of archival documents and manuscripts, as well as practical observation. These methods made it possible to fully and accurately describe the activities of Duysenbek Kabylanbaiuly. During the study, it was established that Islamic traditions were preserved despite Soviet pressure and were transmitted from generation to generation. Duysenbek Kabylanbaiuly’s scholarly works, his collection of religious materials, and their dissemination to society demonstrated effective ways of adapting Islamic teachings. The work contributes to the development of religious consciousness and spiritual enlightenment in Kazakh society, as well as providing a historical understanding of religious heritage and traditions. The results of the study can be applied in the modern system of religious education, spiritual upbringing programs, and activities for preserving cultural and religious heritage. Keywords: educator, religion, traditions, sharia, Islam